Determinants of electronic commerce adoption: Case study among Small and Medium Enterprise (SME) in Klang Valley / Nur Atiqah Zainuddin - Zainuddin, Nur Atiqah (Faculty of Business Management, 2017)
The purpose of this study to determine the factors effect adoption of e-commerce by Small and Medium Enterprise (SME) in Klang Valley. A conceptual framework comprises of five (5) factors (relative advantage, compatibility, complexity, top management support and knowledge and resources constraint). A multivariate likert-scale questionnaire (scale from 1 - 5) has been developed. A sample of 103 respondents has been used from SME in Klang Valley to collect data using SPSS 20. Multiple regression generated to test hypothesis and to establish the causal effect of relative advantage, compatibility, complexity, top management support and knowledge and resources constraint on adoption of e-commerce. Regression analysis was conducted to establish the relative advantage, compatibility, complexity, top management support and knowledge and resources constraint on adoption of e-commerce. The result of the research shows that relative advantage, compatibility, and top management support and knowledge has significant and positive impact on adoption of e-commerce. Therefore this duty concluded that relative advantage, compatibility, and top management support and knowledge would increase adoption of e-commerce among SME in Klang Valley. Therefore, the government should take initiatives and pay more attention to promote e-commerce among SME because SME is economic backbone for the country.